NATURAL ENEMIES AND BIOLOGIES OF THE EGG PARASITOIDS OF TINGIDAE OF SOUTHERN INDIA - LIVINGSTONE, DAVID; YACOOB, M. H. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Natural enemies of the Tingidae have been enumerated. The Chalcid egg parasitoids, reported here from 23 species belonging to 20 genera of Tingidae, are three species of Trichogrammatidae (Lathromeromyia (Lathromeromina) tingiphaga, Lathromeromyia sp., Epoligosita (Epoligositina) duliniae) and two species of Mymaridae (Parallelaptera sp., Erythemelus empoascae). Parallelaptera sp. attacks about 20 species whereas E. (E.) duliniae is specific to Dulinius conchatus. The size of the parasitoid is almost related to the size of the body of the host egg and the length of the ovipositor invariably corresponds with the height of the chorionic collar of the host egg. It is suggested that ecotypic variations in the size and length of the ovipositor of these parasitoids could be considered as an example of biological coevolution of the hosts and the chalcid egg parasitoids in Tingidae. There is no Superparasitism in Tingidae.